Root puppet masters: Infauna shift trait‐productivity relationships in submerged aquatic vegetation communities - Angove, Charlotte; Norkko, Alf; Gustafsson, Camilla (Wiley-Blackwell, 2024)
Submerged aquatic vegetation (SAV) growth can be limited by light and nutrient availability. Infauna are common inhabitants of SAV meadows. Their activity increases nutrient mobility, and they can positively affect plant growth, but we do not know their role in plant trait-biomass production relationships. We approached this problem using a 15-week in situ transplant experiment in the Baltic Sea with experimental additions of Macoma balthica, a sedentary bivalve, to experimental SAV communities. Experimental plant communities were tricultures with varying species composition, compiled from a pool of six different species, to create an experimental gradient of trait community weighted means that allowed us to detect changes more clearly in plant trait-biomass production relationships in response to the M. balthica treatment. We evaluated the relationships between plant height, leaf area, maximum root length (MMRL), specific root length (SRL), and SAV biomass production, then compared M. balthica condition index (soft tissue biomass [WW, mg]/valve length [mm]) to plant community leaf tissue nutrient concentrations (N (%DW), δ15N). Community biomass production was significantly related to plant height in the control treatment, but this relationship was decoupled in the M. balthica treatment, where community biomass production was instead significantly related to MMRL and SRL. This suggested a shift in the predominant SAV growth strategy, from height-related to root-related community biomass production. Leaf tissue δ15N was significantly related to M. balthica condition index. The growth of one species, Potamogeton perfoliatus, was significantly inhibited by the M. balthica treatment. Our results show that infauna have an important role in the plant traits related to community biomass production, and they have the potential to shape plant community structure via selective influences on different plant species.
Keywords: facilitation; functional traits; infauna; SAV; seagrasses